Transformation of Rwanda’s agrifood system structure and drivers - Diao, Xinshen; Ellis, Mia; Rosenbach, Gracie; Mugabo, Serge; Pauw, Karl; Spielman, David J.; Thurlow, James (International Food Policy Research Institute, 2023)
Rwanda has made remarkable economic progress during the past two decades, and its annual GDP growth rate reached more than 7 percent during the 2009 to 2019 period (NISR 2021). The rapid economic growth has been pro-poor, and the poverty rate fell from 58.9 percent in 2000/01 to 38.2 percent in 2016/17 (NISR 2018). The country has also emerged as a leader among sub-Saharan African countries in promoting innovation, gender equality, and an enabling business environment for development. The government remains strongly committed to a set of ambitious development goals, as set forth in the 2017–2024 National Strategy for Transformation (NST 1) and the corresponding sector-level strategic plans. While the global COVID-19 pandemic had a severe adverse effect on the economy, causing negative GDP growth in 2020, the country rebounded quickly and registered more than 10 percent growth in 2021 (NISR 2022). The country was only minimally affected by global commodity market disruptions resulting from the Russia-Ukraine war that started in 2022 and the global recession in 2023 (Arndt et al. 2023; Diao and Thurlow 2023). Looking forward, Rwanda’s GDP growth is projected to reach 6.7 percent in 2023 and 7.0 percent in 2024 (World Bank 2023), suggesting the economy is returning to its pre-pandemic high-growth trajectory.